INDONESIAN GOOD CORPORATE GOVERNANCE IN AN IVORY TOWER: COMMUNICATION ETHICS PERSPECTIVES - Deny Susanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
The implementation of corporate governance that has been running so far tends to be an ivory tower that looks beautiful to look at, but is empty in its contents, such a charming appearance to be seen but is nothing more than makeup and decoration. This is of course a homework shared by all parties, the people as the main stakeholders expect the role and function of the government and the Parliament to grow a figure of trust with high integrity to bring progress to every State Own Enterprise corporation. Key Words: Good Corporate Governance, Communication Ethics, State Own Enterprise